Evaluasi Program AKPAM (Angka Penunjang Akademik Mahasiswa) sebagai Peningkatan Keaktifan Mahasiswi Pesantren di Universitas Darussalam Gontor - Istikomah, Rohmah; Alfi Nur Rosyidah (STAI Ma'had Aly Al-Hikam Malang, 2024)
Islamic boarding schools are one of the developing educational institutions in Indonesia, including Islamic boarding schools for students. Islamic boarding schools as educational institutions need to carry out evaluations related to the programs they undertake, one of which is related to evaluating student academic support numbers programs in increasing female students' non-academic activities. This research article uses a qualitative descriptive method based on field studies. The primary data sources are observations, interviews with Police Force staff and in-depth analysis from interviews at Darussalam Gontor University. The findings of the article are: First, in the implementation of the Akpam program many of the students are based on science, faith and charity. Second, the implementation of the Akpam program aims to increase thought, dhikr, exercise and exercise. Third, the aim of the Akpam program is for students to play an active role in academic and non-academic activities to improve knowledge, faith and charity